Relationship between Body Mass Index (BMI) and Glomerulus Filtration Rate Estimation in Overweight Students at the Health Analyst Department of Pontianak Health Polytechnic - Slamet (POLTEKKES KEMENKES PONTIANAK, 2021)
Obesity occurs due to excessive fat deposits in the body, one of which is a poor diet. The relationship between overweight and chronic kidney disease (CKD) is mediated through several mechanisms of adiponectin, leptin, and resistin, the development of inflammation, oxidative stress, abnormal lipid metabolism, and activation of the renin-angiotensin-aldosterone system. The purpose of this study was to determine the relationship between body mass index and estimated glomerular filtration rate in overweight students at the Health Analyst Department of Pontianak Health Polytechnic. The research design used was cross-sectional. This research was conducted on May 14-18, 2018. The population is a student health analyst. With the criteria for students from the 2015 and 2016 batches who are still active, BMI 23-29.9 Kg/m² and aged 18 to 22 years, totaling 37 respondents. The sampling technique used is total sampling. Performed include measurements of BMI, serum creatinine Jaffe method, fixed time and ELFG Cokroft-Gault formula. The results obtained using the Kendall's tau test showed that the p value (0.906) was greater than (0.05) meaning that there was no relationship between body mass index and estimated glomerular filtration rate in overweight students at the Health Analyst Department of Pontianak Health Polytechnic.